The Relationship Between Serum Apolipoprotein B Levels and Severity of Coronary Lesions Using The Syntax Score in Non-St Segment Elevation Acute Myocardial Infarction Patients at Haji Adam Malik General Hospital Medan - Kesumawardani, Enggar Sari; Safri, Zainal; Hasan, Harris; Hasan, Refli; Andra, Cut Aryfa; Ardini, Tengku Winda (CoinReads Media Prima, 2023)
Introduction: Acute coronary syndrome mainly occurs as a result of plaque rupture of atherosclerosis. Apolipoprotein B (apoB) is a large glycoprotein, playing a role in lipoprotein metabolism and human lipid transport reflecting the number of circulating atherogenic particles. The purpose of this study was to assess the relationship of serum apoB levels with coronary lesion severity. Method: This is a cross-sectional study involving patients who was diagnosed with Non-ST Elevation Myocardial Infarction (NSTEMI) who underwent coronary angiography in November 2021 to July 2022. The NSTEMI criteria follow the Universal Definition of Myocardial Infarction and coronary severity is assessed using a SYNTAX score. Bivariate analysis was conducted looking for the relationship between apoB with SYNTAX scores with p<0.05 considered statistically significant. Results: The subjects of the study is 70 people, dominated by male 50 patients (71.4%). The median age of the subjects was 56 (38-77) years. Median levels of apoB was 107 (32-150) mg/dL. The average SYNTAX score was 25.66 ± 10.83. Using the Pearson correlation test, it was shown that there is a significant correlation between apoB and coronary lesion severity obtained r=0.442 (p<0.001). Conclusion: There is a significant correlation between apoB and coronary lesion severity using SYNTAX scores in NSTEMI patients.